World Economic Outlook, October 2007 : Globalization and Inequality. (World Economic Outlook; World Economic Outlook, 2007)
The global economy grew strongly in the first half of 2007, although turbulence in financial markets has clouded prospects. While the 2007 forecast has been little affected, the baseline projection for 2008 global growth has been reduced by almost 1\2 percentage point relative to the July 2007 World Economic Outlook Update. This would still leave global growth at a solid 4 3/4 percent, supported by generally sound fundamentals and strong momentum in emerging market economies. Risks to the outlook, however, are firmly on the downside, centered around the concern that financial market strains could deepen and trigger a more pronounced global slowdown. Thus, the immediate focus of policymakers is to restore more normal financial market conditions and safeguard the expansion. Additional risks to the outlook include potential inflation pressures, volatile oil markets, and the impact on emerging markets of strong foreign exchange inflows. At the same time, longer-term issues such as population aging, increasing resistance to globalization, and global warming are a source of concern.